Unveiling: The Cause of Academic Stress Among University Students - Dr. Chandana Eswar; Ms. Deepthi Nanjappa (International Journal of Indian Psychȯlogy, 2022)
This cross-sectional study investigates academic stress among university students. It explores the role of demographic factors and, motivations for course enrolment in influencing, stress levels. Data from 129 respondents reveal nuanced insights, with notable variations in stressors among different age groups and motivations for course selection. While the findings underscore the importance of tailored support mechanisms, further research is recommended to comprehensively understand gender-related academic stress degrees. The implications extend to educational institutions and policymakers, emphasizing the need for targeted interventions. The study provides a foundation for future research, urging a comprehensive examination of the root causes of disparities in academic stress levels and the development of effective solutions.